2018
DOI: 10.31015/jaefs.18021
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path coefficient analysis for grain yield and its attributing traits of maize inbred lines (Zea mays L.) under heat stress condition

Abstract: Heat stress during the flowering, pollination and grain filling periods affect maize grain yield and its attributing  traits. Twenty maize inbred lines were evaluated in alpha lattice design with two replications under heat condition during spring season from February to June, 2016 at Rampur, Chitwan, Nepal. Meterological data showed maximum mean temperature (46.2–43.28ºC) and minimum (30.52-30.77ºC) in with relative humidity 37.05 to 49.45% inside the tunnel during in April-May which coincided with the flower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
8
12
2
Order By: Relevance
“…Existence of genetic variability among maize genotypes for yield and major yield attributing traits were reported by Bhusal et al (2017), Kandel et al (2018), Sharma et al (2018) and Adhikary et al (2018).…”
Section: Grain Yield and Yield Attributing Traitsmentioning
confidence: 68%
“…Existence of genetic variability among maize genotypes for yield and major yield attributing traits were reported by Bhusal et al (2017), Kandel et al (2018), Sharma et al (2018) and Adhikary et al (2018).…”
Section: Grain Yield and Yield Attributing Traitsmentioning
confidence: 68%
“…Thus there is scope to enhance genetic yield potential through selection and hybridization. Existence of significant genetic variability among maize genotypes for yield and major yield attributing traits were reported by Vashistha et al (2013), Ogunniyan and Olakojo (2014), Pahadi and Sapkota (2016), Bhusal et al (2017), Kandel et al (2018) and Sharma et al, (2018). Prasai et al (2015) also reported genetic variability on early maize.…”
Section: Analysis Of Variancementioning
confidence: 71%
“…The relationship among different traits in wheat can be determined using genotypic and phenotypic correlation analysis. It is an effective tool for the enhancement of crop improvement for traits of interest [1][2][3]. The correlation coefficient among traits shows a complex chain of interacting relationships and the direction of the relationship.…”
Section: Introductionmentioning
confidence: 99%